Influencia de la temperatura de tostación en la extracción de oro por cianuración de un concentrado gravimétrico aurífero carbonáceo - Lázaro Rodríguez, Erick Jhon (2023)
The influence of the roasting temperature of carbonaceous gold concentrates obtained by gravimetric concentration and then leached with sodium cyanide to extract the gold was evaluated. The carbonaceous head mineral presented a gold extraction of 27.70% gold and the carbonaceous concentrate extracted 33.60% gold, therefore, they present a preg robbing effect, and are considered refractory minerals due to the low gold extraction. The roasting sample was a carbonaceous gold concentrate obtained by centrifugal gravimetric concentration with a grade of 63.26 g/t gold. A unifactorial design was applied, with the roasting temperature factor at levels of 600°C, 700°C and 800°C, then the gold calcines obtained were cyanided by bottle leaching to extract the gold. From the results obtained in bottle cyanidation at 600°C 95.91% gold is extracted, at 700°C 76.61% gold is extracted and 800°C 69.44% gold is extracted. This means an increase of 62.31%, 43.01% and 35.84% respectively with respect to the uncalcined concentrate. It is concluded that the roasting temperature variable significantly influences the percentage of gold extraction by cyanidation of the calcines obtained from a carbonaceous concentrate.